Modelling batch microwave heating of water - Yeong, S.; Law, M.; Vincent Lee, C.; Chan, Stephanie (2017)
A numerical model of the microwave heating of distilled water is developed using COMSOL Multiphysics software to investigate the microwave effects on the heating rate. Three frequencies (0.915GHz, 2GHz and 2.45 GHz) have been applied in the model in order to study their influences on the water temperature. It is found that the water heats up at 2GHz and 2.45GHz, however, there is no sign of heating at 915MHz. This is supported with the figures of the electric field distribution in the microwave cavity. The results shown in the developed model is validated with the experimental results obtained at 2.45 GHz.